Implementing quality: - Basu, Ron (Thomson, 2004)
The methodology of implementing a quality management and improvement programme can be varied. The programme is likely to have a different name or label, such a TQM ( total quality management), six sigma, learn sigma, BPR (business process re-engineering) or operational excellence